PENYEMPURNAAN SIFAT PAPAN SERAT KERAPATAN SEDANG DARI PELEPAH NIPAH DAN CAMPURANNYA DENGAN SABUT KELAPA - Dian Anggraini Indrawan; Han Roliadi; Rossi Margareth Tampubolon; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2013)
Nowadays, the potency of conventional fibrous materials (ie, woods) for the manufacture of medium-density fiberboard (MDF) becomes depleted and scarce. Use of alternative fibers which are abundantly available and still largely unutilized, i.e. nypha midribs and coconut coirs, bas been attemped for MDF (medium-density fiberboard), using urea-formaldebryde (UF) adhesive However, such study showed that MDV from each of the two fiber sources could not satisfy the JIS and ISO standards. In relevant, improvement trial on MDF properties was accomplished using both kinds of fibers. Intially, those fiber stuffs had their basic properties examined, i.e. specific gravity, chemical composition, and fiber dimensions and their derived values. The MDF's fibrous pulping employed a bat semi-chemical soda process under atmospheric pressure at two alkali concentrations (8% and 12%). The resulting pulps were then added with additives, i.. 5% alum, 5% tannin formaldebryde (TF) adbesive either incorporated with activated charcoal (5%) or not; and then shaped into MDF mat using wet process, Physical-strength properties and formaldebryde emission of the resulted MDF wery examined. Assessing those properties, nypa-midrib fibers were more prospective for MDF than coconut-coir fibers, Activated- charcoal addition lowered MDF's formaldehyde emistion and improved dimensional stability, but decreased its strengths. In properties, MDF, from nypa fibers 100% were significantly the closest in satisfying the standard (JIS and LSO). Yet, coconut-enir fibers could still be prospective for MDF by missing them (pulp form) with wypa-fiber pulp at the propertion (w/w): 25%+75% and 50%+50%. The MDF with TF adhesive afforded better properties than the previous experiment (UF), n. greater strengths, lowered emotion and satisfying more of the 115 and ISO standard.